The Design of Website Application for Fast-Track Registration of the Javanese Language Education Study Programme (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
Enhancing student engagement with fast-track programmes requires an efficient and accurate registration system. This study aims to design and develop a web application to automate this process. Employing a qualitative descriptive methodology, the research first identifies the operational conditions and requirements within the institutional context. The development itself follows the Rapid Application Development (RAD) model. The resulting application significantly improves registration efficiency, minimizes data entry errors, and enhances the user experience for applicants. Key features include an online registration form, automated data verification, a registration status tracker, and a notification system. Furthermore, the application is integrated with the existing academic information system. Consequently, the developed web application presents an effective solution for streamlining the fast-track registration process, thereby improving operational effectiveness and providing superior service to prospective participants.